2011
DOI: 10.4103/0976-9668.82313
|View full text |Cite
|
Sign up to set email alerts
|

A scientometric analysis of Indian research output in medicine during 1999-2008

Abstract: Objective:This study analyzes the research activities of India in medicine during 1999–2008, based on the total publication output, its growth rate, quality of papers published and rank of India in the global context. Patterns of international collaborative research output and the major partner countries of India are also discussed. This study also evaluates the research performance of different types of Indian medical colleges, hospitals, research institutes, universities and research foundations and the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 8 publications
1
35
0
Order By: Relevance
“…Table 4 shows the data from the 12 most productive countries in biomedicine and health sciences and compares the data for general productivity in the psychiatry and neurology disciplines, with productivity in the specific field of AADs. Our results are similar to those reported by Gupta and Bala [13] ; according to this study, India holds 12 th rank among the productive countries in medicine research consisting of 65,745 papers with a global publication share of 1.59% [46] . It is worth nothing that countries such as India, Spain and Canada sit near the top of the ranking for producing publications on AADs (see also Figure 4).…”
Section: Discussionsupporting
confidence: 82%
“…Table 4 shows the data from the 12 most productive countries in biomedicine and health sciences and compares the data for general productivity in the psychiatry and neurology disciplines, with productivity in the specific field of AADs. Our results are similar to those reported by Gupta and Bala [13] ; according to this study, India holds 12 th rank among the productive countries in medicine research consisting of 65,745 papers with a global publication share of 1.59% [46] . It is worth nothing that countries such as India, Spain and Canada sit near the top of the ranking for producing publications on AADs (see also Figure 4).…”
Section: Discussionsupporting
confidence: 82%
“…4 Scientometric analysis of research areas enable studying the growth of a research field and helps in identifying prominent authors, institutes, etc. Such studies have been carried out in many areas [5][6][7] ; however, an analytical study on zebrafish research output has not been carried out so far. A scientometric study of this important organism will enable us to understand the trends in zebrafish research as we use this model organism to explore new research frontiers.…”
Section: Introductionmentioning
confidence: 99%
“…This investigation showed that the India rank was the twelfth among world scientific productions about medicine. More India's scientific contributions in Medicine associated with the Cancer and Cardiovascular diseases and were introduced as highly cited articles according to the citation of 100 articles [8]. Kaue studied India's programs in pharmacology, toxicology and pharmaceutics from 1998 to 2007, based on several parameters, including the country annual average growth rate, sharing and ranking of global publication, and international collaboration [3].…”
Section: Introductionmentioning
confidence: 99%